A short review of the distribution of short-beaked common dolphins (Delphinus delphis) in the central and eastern North Atlantic with an abundance estimate for part of this area - Canadas, Ana Maria; Donovan, Greg P; Desportes, Geneviève; Borchers, David Louis (NAMMCO Scientific Publications, 2018)
This paper uses data from 3 programmes: (1) the North Atlantic Sightings Surveys (NASS) surveys undertaken throughout much of the central and eastern North Atlantic north of about 40° N in 1987, 1989, 1995 and 2001; (2) the MICA-93 programme; and (3) the north eastern Atlantic segment of the Small Cetacean Abundance in the North Sea (SCANS) survey in 1994. The data from all surveys were used to examine the distribution of common dolphins in the NE Atlantic. No sightings were made north of 57° N. An initial attempt to examine distribution against 4 potential non biological explanatory variables was made. A simple interpretation of the preliminary analyses presented here is that the primary areas for groups of common dolphins were in waters over 15° C and depths of 400-1,000 m (there does appear a link with shelf features), between around 49°-55° N especially between 20°-30°W. An illustrative example of spatial modelling is presented. Only for 1 year (and part of the total survey area) were there sufficient data to attempt to estimate abundance: 1995. The estimated abundance in the W Block of the NASS-95 Faroese survey was 273,159 (cv=0.26; 95% CI=153,392-435,104) short-beaked common dolphins. This estimate is corrected for animals missed on the trackline (g(0)) and for responsive movement. Peer reviewed